DISIPLIN PASAR DAN PENGATURAN PERBANKAN: KOMPLEMEN ATAU SUBSTITUSI? - MUAZAROH MUAZAROH (Universitas Islam Nahdlatul Ulama Jepara, 2010)
ABSTRACT The banking crises over the fast two decades around the world has renewed the interest in market discipline in banking systems This Interest is not merely academic, but it also apparent in recent poffcy initiatives such as the latest capital proposal by The Basel Commitee on Banking Supervision. The new Basel Capital Accord has 3 pillars. Pillar 3 is disclosure requirement to enhance market discipline. Market discipline has the potential to reinforce pillar 1 ( minimum capital standar) and pillar 2 (supervisory review process) and promote safety and soundness in banks and financial systems. The first objective of this paper Is to explain bank regulatory and the important of Jnarket discipline to complement bank regulatory. The second objective is to explain the framework of market discipline theory and ask some issue: what is market discipline, why the calf for market discipline, how market discipline relates to agency conflict In finance theory and how Is the framework of market discipline in banking. The third objective is to review some empirical research in market discipline. Keywords : Banking Crises, Moral Hazard, Market Discipline and Bank Reg